Question
upstudy study bank question image url

If \( f(x)=4 x^{\wedge} 2-7 x+3 \) and \( g(x)=x-2 \), find in simplest form: (a) \( f(x)+g(x)(1 \) Mark) (b) \( f(x)-g(x)(2 \) Marks \( ) \) (c) \( f(x) \times g(x)(2 \) Marks \( ) \) (d) Solve for \( x \) in the equation \( f(x)=g(x) \). (3 Marks)

Ask by Murphy Kelley. in Australia
Mar 22,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

**(a)** \( f(x) + g(x) = 4x^2 - 6x + 1 \) **(b)** \( f(x) - g(x) = 4x^2 - 8x + 5 \) **(c)** \( f(x) \times g(x) = 4x^3 - 15x^2 + 17x - 6 \) **(d)** The solutions for \( f(x) = g(x) \) are \( x = 1 + \frac{i}{2} \) and \( x = 1 - \frac{i}{2} \).

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Answered by UpStudy AI and reviewed by a Professional Tutor

Extra Insights

To solve the problem, let’s break it down step by step. Given: \( f(x) = 4x^2 - 7x + 3 \) \( g(x) = x - 2 \) ### (a) \( f(x) + g(x) \) To add the functions, we substitute them into the expression: \[ f(x) + g(x) = (4x^2 - 7x + 3) + (x - 2) \] Combining the terms: \[ = 4x^2 - 7x + x + 3 - 2 \] \[ = 4x^2 - 6x + 1 \] So, the answer is: \( \boxed{4x^2 - 6x + 1} \) ### (b) \( f(x) - g(x) \) Now for the subtraction: \[ f(x) - g(x) = (4x^2 - 7x + 3) - (x - 2) \] Again combining the terms: \[ = 4x^2 - 7x + 3 - x + 2 \] \[ = 4x^2 - 8x + 5 \] So, the answer is: \( \boxed{4x^2 - 8x + 5} \) ### (c) \( f(x) \times g(x) \) Now, let’s multiply the two functions: \[ f(x) \times g(x) = (4x^2 - 7x + 3)(x - 2) \] Using the distributive property (also known as the FOIL method for binomials): \[ = 4x^2 \cdot x + 4x^2 \cdot (-2) - 7x \cdot x - 7x \cdot (-2) + 3 \cdot x + 3 \cdot (-2) \] \[ = 4x^3 - 8x^2 - 7x^2 + 14x + 3x - 6 \] \[ = 4x^3 - 15x^2 + 17x - 6 \] So, the answer is: \( \boxed{4x^3 - 15x^2 + 17x - 6} \) ### (d) Solve for \( x \) in the equation \( f(x) = g(x) \) This means we need to set \( f(x) \) equal to \( g(x) \): \[ 4x^2 - 7x + 3 = x - 2 \] Rearranging gives: \[ 4x^2 - 7x - x + 3 + 2 = 0 \] \[ 4x^2 - 8x + 5 = 0 \] Now we can use the quadratic formula \( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \), where \( a = 4, b = -8, c = 5 \): Calculating the discriminant: \[ b^2 - 4ac = (-8)^2 - 4 \cdot 4 \cdot 5 = 64 - 80 = -16 \] Since the discriminant is negative, there are no real solutions. Therefore, the solutions are complex: \[ x = \frac{8 \pm \sqrt{-16}}{8} = \frac{8 \pm 4i}{8} = 1 \pm \frac{1}{2}i \] So, the answer is: \( x = 1 + \frac{1}{2}i \) or \( x = 1 - \frac{1}{2}i \) Thus, the final answers are: (a) \( \boxed{4x^2 - 6x + 1} \) (b) \( \boxed{4x^2 - 8x + 5} \) (c) \( \boxed{4x^3 - 15x^2 + 17x - 6} \) (d) \( \boxed{1 + \frac{1}{2}i}, \, \boxed{1 - \frac{1}{2}i} \)

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy